Implementasi Pendekatan Culturally Responsive Teaching (CRT) Berbasis Kearifan Lokal Jawa dalam Pembelajaran Bahasa Indonesia Kelas IV di SD Negeri Randusari - Layinatus Sifa; Eko Handoyo; Indriana Eko Armaidi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
ABSTRACT Indonesia's cultural diversity needs to be preserved through education by integrating local wisdom into the learning process. However, learning activities in schools are often less contextual because they do not adequately consider students' cultural backgrounds. This study aimed to describe the implementation of Culturally Responsive Teaching (CRT) based on Javanese local wisdom and to identify students' responses and engagement during the learning process. This research employed a qualitative descriptive approach. The study was conducted in Grade IV of SD Negeri Randusari involving 16 students. Data were collected through observation, documentation, and learning reflection, and analyzed using data reduction, data display, and conclusion drawing techniques. Data validity was ensured through source and technique triangulation. The findings revealed that CRT was implemented by integrating Javanese local wisdom into Indonesian language learning through the use of the traditional song Suwe Ora Jamu, culture-based learning media, and learning activities connected to students' cultural experiences. The implementation of CRT created contextual and meaningful learning experiences. Students showed positive responses and active engagement during learning activities, including group discussions, problem-solving, presentations, and reflections. In addition, the integration of local culture contributed to the development of cultural awareness and appreciation of local cultural heritage. Therefore, CRT based on Javanese local wisdom can serve as an effective learning approach to create active, meaningful, and culturally responsive learning in elementary schools. Keywords: Culturally Responsive Teaching, Javanese Local Wisdom, Indonesian Language Learning